Engagement of the inhibitory receptor CD158a interrupts TCR signaling, preventing dynamic membrane reorganization in CTL/tumor cell interaction. - Guerra, N; Michel, F; Gati, A; Gaudin, C; Mishal, Z; Escudier, B; Acuto, O; Chouaib, S; Caignard, A (2002)
Renal cell carcinoma (RCC) infiltrating lymphocytes (TILs) express killer cell immunoglobulinlike receptors (KIRs) that inhibit the antitumor CD8(+) T-cell lysis. In the present study, to better examine the functional consequences of KIR engagement on cytotoxic T lymphocyte (CTL)/tumor interaction, we have investigated the influence of KIR CD158a on early steps of T-cell activation. We show that coengagement of T-cell receptor (TCR) and CD158a by tumor cells inhibited tyrosine phosphorylation of early signaling proteins ZAP-70 and LAT, lipid raft coalescence, and TCR/CD3 accumulation at the CTL/tumor cell interface. In addition, the guanine exchange factor Vav was not phosphorylated, and no actin cytoskeleton rearrangement was observed. Our data indicate a role of KIR CD158a in the dynamic events induced by TCR triggering, preventing CTL membrane reorganization, and subsequent completion of CTL activation program. Accordingly, the expression of CD158 by TILs may favor tumor cell escape to the immune response.